Quality of Institutions, Global Sourcing, and the Make-or-Buy Decision - Bohdan Kukharskyy (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2012)
Do contractual institutions and a country's level of trust interact in their impact on the international make-or-buy decision? By analyzing explicit and implicit contracting in a unified framework, I show that better formal contractibility may both facilitate and hinder relational contracting on a trust basis. If formal agreements crowd out first-best efficient relational contracts, firms' profitability and consumers' welfare decrease. In contrast, a higher level of trust unambiguously increases firm performance and a country's attractiveness as an offshoring destination. I also show that improvements in the trust level are associated with largest reductions in intrafirm trade if formal contractibility is low. Lastly, this paper argues that models built on the simplifying assumption of ex ante lump-sum transfers between parties generally overestimate the prevalence of outsourcing vs. integration.
Keywords: D02; D23; F14; L22; 330; International organization of production; institutional quality; relational contracting; interaction of explicit and implicit contracts; welfare